Amantadine resistance among highly pathogenic avian influenza viruses (H5N1) isolated from India. (February 2016) - Jacob, Aron; Sood, Richa; Chanu, Kh. Victoria; Bhatia, Sandeep; Khandia, Rekha; Pateriya, A.K.; Nagarajan, S.; Dimri, U.; Kulkarni, D.D.
Abstract: Emergence of antiviral resistance among H5N1 avian influenza viruses is the major challenge in the control of pandemic influenza. Matrix 2 (M2) inhibitors (amantadine and rimantadine) and neuraminidase inhibitors (oseltamivir and zanamivir) are the two classes of antiviral agents that are specifically active against influenza viruses and are used for both treatment and prophylaxis of influenza infections. Amantadine targets the M2 ion channel of influenza A virus and interrupts virus life cycle through blockade of hydrogen ion influx. This prevents uncoating of the virus in infected host cells which impedes the release of ribonucleoprotein required for transcription and replication of virion in the nucleus. The present study was carried out to review the status of amantadine resistance in H5N1 viruses isolated from India and to study their replicative capability. Results of the study revealed resistance to amantadine in antiviral assay among four H5N1 viruses out of which two viruses had Serine 31 Asparagine (AGT—AAT i.e., S31N) mutation and two had Valine 27 Alanine (GTT—GCT i.e., V27A) mutation. The four resistant viruses not only exhibited significant difference in effective concentration 50% (EC50 ) values of amantadine hydrochloride from that of susceptible viruses (P < 0.0001) but also showed significant difference between two different types (S31N and V27A) of mutant viruses (P < 0.05). Resistance to amantadine could also be demonstrated in a simple HA test after replication of the viruses in MDCK cells in presence of amantadine. The study identifies the correlation between in vitro antiviral assay and presence of established molecular markers of resistance, the retention of replicative capacity in the presence of amantadine hydrochloride by the resistant viruses and the emergence of resistant mutations against amantadine among avian influenza viruses (H5N1) without selective drug pressure. Highlights: Resistance to amantadine was identified among four H5N1 viruses isolated in India. Two viruses with S31N mutation had higher EC50 of amantadine than the two with V27A. Resistant viruses replicated in vitro at peak non-toxic concentration of the drug. Resistance was also shown by HA after in vitro growth of viruses with amantadine.